Ultra-thin heat sink and manufacturing method thereof

By using a liquid absorbent core composed of porous medium or loose capillary layer and a porous metal support layer with a three-dimensional three-dimensional mesh structure, combined with a closed chamber structure, the problems of consistency and heat transfer performance in the manufacturing process of the existing heat-smooth heat-smooth plate are solved, and efficient heat transfer and structural stability of the ultra-thin heat-smooth plate are achieved.

CN111465293BActive Publication Date: 2025-03-07WUZHOU HGP ADVANCED MATERIALS TECH CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202010415546.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-05-16
Publication Date
2025-03-07
Estimated Expiration
2040-05-16

AI Technical Summary

Technical Problem

It is difficult to ensure consistency during the manufacturing process of existing heat-smoothing plates, the heat transfer performance is limited, and the liquid absorbing core is difficult to meet the requirements of thin thickness, large capillary suction and high permeability at the same time.

Method used

An ultra-thin closed chamber structure consisting of an upper shell plate, a lower shell plate, a liquid absorbent core, a porous metal support layer and a working medium is adopted. The liquid absorbent core is composed of a porous medium or a loose capillary layer. The porous metal support layer has an open three-dimensional three-dimensional mesh structure and is formed by rolling processing to form a patterned structure.

Benefits of technology

It realizes efficient heat transfer and diffusion of ultra-thin heat-smoothing plates, improves heat transfer performance and structural stability, and can produce heat-smoothing plates with an overall thickness of less than 1mm.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN111465293B_ABST
    Figure CN111465293B_ABST
Patent Text Reader

Abstract

The present invention discloses an ultra-thin heat spreader and a manufacturing method thereof. A porous medium with different structures, thicknesses and pores is used as a liquid wick connected to the inner surface of an upper shell plate and a lower shell plate of different thicknesses, and an ultra-thin heat spreader is made through welding, vacuuming, liquid injection, packaging and other processes. The middle steam chamber of the heat spreader uses a porous metal with a single structure or a patterned structure as a support layer to ensure that the working medium flows rapidly after gasification and promotes rapid reflux after the phase change of gas to liquid phase, thereby accelerating the phase change cycle of the working medium. The present invention can prepare a component with good capillary suction, permeability and high thermal conductivity by regulating the structure and internal gap of the liquid wick and the porous metal support layer. The heat spreader thus manufactured has high heat dissipation efficiency, light weight and good reliability, is suitable for manufacturing ultra-thin structures, can meet the requirements of high thermal conductivity and ultra-thinness required for electronic equipment with high heat flux density, and can be prepared through a roll-to-roll continuous production process, with extremely high production efficiency, and is very suitable for large-scale industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of heat conduction technology, and relates to a vapor chamber technology, and in particular to an ultra-thin vapor chamber and a manufacturing method thereof. Background Art

[0002] The miniaturization of electronic devices has become the mainstream trend in the development of modern electronic devices. The characteristic size of electronic devices continues to decrease (for example, the characteristic size of microprocessors decreased from 0.35 µm to 0.18 µm from 1990 to 2000), and the integration, packaging density and operating frequency of chips continue to increase, which has rapidly increased the heat flux density of chips. Studies have shown that more than 55% of the failure forms of electronic devices are caused by excessive temperature, so the thermal reliability design of electronic devices plays a vital role in the development of electronic devices.

[0003] With the increasing integration and thinness of electronic products such as mobile phones, tablets, OLED TVs, and smart wearable devices, people expect products to have a thinner and lighter appearance, as well as higher computing speeds and better multimedia performance to meet the requirements of high-speed, portable, mobile work or mobile entertainment. Under the strong guidance of the market demand, electronic devices are constantly developing in the direction of high frequency, high speed, and dense and miniaturized integrated circuits, which has led to a sharp increase in the power consumption of electronic devices per unit volume, resulting in a rapid increase in heat generation, and higher and higher performance requirements for heat dissipation devices. Traditional heat dissipation materials such as metal foils and graphite sheets can no longer meet the requirements.

[0004] A heat pipe is a phase change heat transfer device with high thermal conductivity and heat transfer power. When the heat pipe is working, it transfers the heat flow of the heat source from the evaporation end to the condensation end, and then transfers it from the condensation end to the heat sink with a larger surface area by heat conduction. Finally, the heat is taken away by convection heat transfer. Its thermal conductivity is dozens to hundreds of times that of existing metal materials. However, conventional heat pipes are above the millimeter level from diameter to thickness, which is difficult to adapt to the narrow space in a mobile phone. For example, the thickness of a laptop or tablet computer has been reduced by 10mm, the thickness of a mobile phone is generally below 8mm, and the heat dissipation gap of a fuel cell is only 3mm. Currently, the commonly used cylindrical heat pipes or flattened heat pipes can hardly meet the heat dissipation requirements of compact high-power electronic devices, which has prompted the heat pipe to develop in the direction of lightness and thinness. However, as the thickness of the heat pipe decreases, the interface shear force caused by the internal vapor-liquid high-speed convection will increase, and the heat transfer capacity will be limited. Therefore, while ensuring ultra-thinness, the heat pipe must also have a strong heat transfer capacity. This is a difficulty in the field of ultra-thin heat pipes and a hot spot in the field of heat pipe research.

[0005] When designing modern smartphones, tablet computers and other devices, the thickness reserved for heat dissipation devices is very small, mostly less than 1mm. In such a thin heat pipe, separate gas-liquid channels must be set inside to ensure efficient heat transfer of gas-liquid circulation during operation, which places very high requirements on the design and manufacturing process of ordinary heat pipes. Due to the shape of the heat pipe, it mainly realizes one-dimensional heat transfer from the heat source to the heat sink. In most electronic components, heat transfer on a two-dimensional plane is more common. For two-dimensional plane heat dissipation, another phase change heat transfer element, the vapor chamber, came into being. The vapor chamber is a type of flat heat pipe that can quickly transfer and diffuse the heat flux gathered on the surface of the heat source to a large area of ​​condensation surface, thereby promoting heat dissipation, reducing the heat flux density on the surface of the component, and ensuring its reliable operation. Due to its low thermal resistance, good temperature uniformity and high critical heat flux density, the vapor chamber is currently widely used in the heat dissipation of electronic components such as high-power LEDs, CPUs, GPUs, and high-speed hard disks.

[0006] In the prior art, the wick of the heat spreader is generally a sintered copper powder type or a metal wire mesh. In the manufacturing process of the heat spreader using the sintered copper powder wick, metal powder needs to be filled into a thin-walled metal tube and then sintered. The production process is very difficult and consistency is difficult to ensure. During high-temperature sintering, wrinkles are very likely to appear due to the different thermal expansion coefficients of the metal shell layer and the copper powder sintered layer. For the heat spreader using metal wire mesh, since the wire mesh structure has a high permeability but low capillary force, and the single-layer wire mesh is prone to cracking when sintered and the thickness is too small, resulting in too little work quality, a multi-layer structure is often used in general wire mesh sintering. The multi-layer sintered wire mesh structure is prone to poor contact between layers, which weakens the heat transfer performance.

[0007] Foam metal is a porous material with a high porosity, which is generally above 70% and can even reach 98%, and it is relatively easy to adjust the pore size and porosity. The high porosity makes the foam metal wick have a high permeability, which can effectively reduce fluid resistance; foam metal has a large specific surface area, which can increase the contact area between the wick and the working fluid, which is beneficial to the evaporation of the working fluid and reduces the evaporation thermal resistance; foam metal also has the characteristics of low density, weighing only 20-60% of the same volume of metal, and the thickness can be as low as 0.2mm, so it can effectively reduce the conduction thermal resistance and is expected to be widely used in ultra-thin heat sinks.

[0008] The Chinese patent (CN 104764350) discloses a "method for manufacturing a heat soaking plate with foam copper as a liquid wick". The foam copper (thickness 0.1mm-3mm, pore size 300nm-1000μm, porosity 40%-95%) is sintered on an upper cover plate and a lower base plate made of corresponding copper plates or copper foils of different thicknesses as a liquid wick. The middle steam chamber uses a cylindrical or square foam copper with a certain thickness (≥0.8mm) as a support column. After welding, vacuuming, liquid injection, and packaging, the heat soaking plate is made. The diameter of the support column is 3-8mm, and the interval between the support columns is 10-15mm.

[0009] The Chinese patent (CN 104896983) discloses "a method for manufacturing a heat spreader with ultra-thin foam silver as a liquid wick", which uses foam silver (thickness 0.1mm-2mm, pore size 300nm-1000μm, porosity 40%-95%) sintered on an upper cover plate and a lower base plate made of corresponding pure copper plates or copper foils of different thicknesses as a liquid wick, and the middle steam chamber uses a cylindrical or square foam silver or copper with a certain thickness (≥0.8mm) as a support column, and the heat spreader is made through welding, vacuuming, liquid injection, packaging and other processes. The diameter or size of the support column is 2-8mm, and the interval between the support columns is 8-15mm. Separate support columns are difficult to produce continuously on a large scale.

[0010] In the above two prior arts, foam metal is used as the liquid absorption core and support column. The function of the support column is to support the middle steam cavity so that the structure of the heat spreader does not collapse after vacuum degassing. Since the interval between the support columns (8-15mm) is relatively large, if relatively thin copper foil is used as the upper and lower cover plates, the copper foil will be dented in the interval between the support columns, affecting the thermal conductivity of the heat spreader. Therefore, the thickness of the cover plate used cannot be less than 0.1mm. This structure limits the thickness of the heat spreader.

[0011] In addition, the foam metal absorbent core used in the prior art is composed of interconnected holes with different pore size distributions. The holes in the inner layer of the foam are complete micropores, while the holes in the outermost layer are broken and attached to the outer layer of the complete holes in a form similar to a microcolumn structure. Its effective wicking radius is larger than the effective radius of the inner layer, and its capillary force is smaller than that of the inner layer. Therefore, in order to obtain the good characteristics of the foam metal absorbent core, at least one layer of complete pore channels must be retained inside it. If a foam metal absorbent core with a relatively large pore size is used for high permeability, the thickness of the absorbent core will be relatively thick, and the capillary force of the absorbent core will decrease; if a foam metal absorbent core with a very small pore size is used for lower thickness and greater capillary suction, the flow resistance of the liquid inside the capillary core will be very large, thereby reducing the heat transfer capacity of the heat spreader.

[0012] It is difficult for the existing absorbent core to simultaneously meet the three characteristics of thin thickness, strong capillary suction, and high permeability. When using ultra-thin upper and lower shell plates, or making a heat spreader with ultra-thin thickness (<1mm), it is difficult to support the structure of the heat spreader without collapsing using independent separate support columns. Summary of the invention

[0013] The present invention discloses an ultra-thin heat spreader and a manufacturing method thereof. The ultra-thin heat spreader can quickly transfer heat from a heat source to a heat sink in one dimension like a common heat pipe, and can also quickly diffuse heat radially in a two-dimensional plane.

[0014] The technical solution of the present invention is:

[0015] An ultra-thin heat spreader, the structure of which is an ultra-thin closed chamber composed of an upper shell plate, a lower shell plate, a liquid wick, a porous metal support layer and a working medium, characterized by:

[0016] (1) The thickness of the upper shell plate and the lower shell plate is 0.01 mm to 1.0 mm, and the material is metal and its alloy or non-metal and compound material with good thermal conductivity and airtightness;

[0017] (2) The thickness of the liquid absorbent core is 0.02 mm to 1.5 mm, and it is composed of at least one of the following four materials: a porous medium obtained by sintering metal powder with an average particle size of 0.01 mm to 0.5 mm; or a loose porous capillary layer obtained by electroplating on the inner surface of the upper shell plate and the lower shell plate; or a porous medium obtained by compressing one or more layers of foam metal with an average thickness of 0.4 mm to 3 mm, and the porosity of the foam metal after compression is 30% to 90%; or a porous medium obtained by filling metal powder with an average particle size of 0.01 mm to 0.5 mm into one or more layers of foam metal, and sintering the porous medium, and the porosity of the porous medium obtained after sintering is 30% to 90%;

[0018] (3) The porous metal support layer has an open-pore three-dimensional mesh structure with a thickness of 0.1 mm to 15 mm. The structure can be a patterned structure or a single structure, wherein: the patterned structure refers to a groove provided on the porous metal support layer, the groove depth is 0.02 mm to 14.5 mm, the groove bottom width is 0.05 to 30 mm, and the groove top width is 0.05 to 30 mm; the single structure refers to a porous metal with uniform thickness and no local compression or local mechanical thinning processing;

[0019] (4) The working medium is filled in the closed inner cavity of the shell. The working medium is a liquid material, and its volume accounts for 50% to 300% of the void space of the liquid absorbent core.

[0020] The upper and lower shell plates are made of any one of copper, aluminum, silver, nickel, titanium, carbon material, mica, and boron nitride, or a composite material made of any two or more of them, or a copper alloy, aluminum alloy, silver alloy, nickel alloy, titanium alloy material; or a composite material composed of any one of graphite, diamond, mica, and boron nitride;

[0021] The metal powder is a single metal material formed by any one of copper, aluminum, silver, nickel and titanium, or a copper alloy, aluminum alloy, silver alloy, nickel alloy and titanium alloy material, or a multilayer composite material with the aforementioned materials as the matrix and surface coating or coating.

[0022] The two or more layers of superimposed foam metals used to form the liquid absorbent core can be made of the same material and specification, or can be made of different pore numbers (PPI), thickness, surface density, and material;

[0023] The grooves of the patterned structure of the porous metal support layer may be arranged parallel to the length or width direction, or arranged at a specific angle to the length or width direction, or intersecting each other on the porous metal support layer, or arranged radially outward with a certain point as the center point on the porous metal support layer.

[0024] The porous metal support layer is a porous foam metal with an open-pore three-dimensional network structure obtained by depositing a metal layer on the surface of a polyurethane sponge and then sintering and reducing it.

[0025] The volume of the working medium accounts for 80%-150% of the void space of the wick.

[0026] The working medium is any one of the following materials or a mixture thereof: ammonia, freon, ethane, acetone, butanone, water, ethanol, methanol, toluene, Thermal Conductivity-A, Thermal Conductivity-E.

[0027] The liquid-absorbing core includes a hydrophilic metal oxide nanostructure on its surface, and the morphology of the metal oxide nanostructure includes at least one of nanowires, nanoparticles, and nanosheets;

[0028] The upper and lower shell plates include metal sheets obtained through rolling and electrolysis processes, or single crystal metals obtained by heat treatment of rolled metal sheets, or liquid metals.

[0029] The carbon material includes artificial graphite, natural graphite or diamond.

[0030] The artificial graphite comprises a composite material obtained by depositing a metal layer on the surface of an artificial synthetic graphite sheet by vacuum plating, electrodeposition or a combination of the two processes, wherein the artificial synthetic graphite sheet is made of a polyimide film (abbreviated as PI) through high-temperature carbonization and graphitization treatment.

[0031] The metal layer refers to any material of copper, tin, silver, and titanium, or a composite material made of any two or more of them.

[0032] A method for manufacturing an ultra-thin vapor chamber, characterized in that it comprises the following process steps:

[0033] 1. Production of upper and lower shell plates;

[0034] (ii) The liquid absorbent core is manufactured by at least one of the following methods: sintering metal powder with an average particle size of 0.05 mm to 0.5 mm; or a loose and porous capillary layer obtained by electrodeposition on the inner surface of the upper shell plate and the lower shell plate; or compressed by one or more layers of foam metal with an average thickness of 0.4 mm to 3 mm; or filling metal powder with an average particle size of 0.05 mm to 0.5 mm into one or more layers of foam metal and sintering under pressure;

[0035] (3) connecting the metal sheets serving as the upper shell plate and the lower shell plate to the liquid wick;

[0036] (iv) Preparation of porous metal support layer;

[0037] (5) placing the porous metal support layer between the upper and lower shell plates connected to the wick;

[0038] (vi) Assemble using welding technology, weld the upper and lower shell plates together around the perimeter, and reserve a liquid filling port;

[0039] (VII) Filling the working medium into the closed inner cavity between the upper and lower shell plates;

[0040] (8) Welding seal.

[0041] In the process of manufacturing the absorbent core, when the absorbent core is obtained by compressing the foam metal, the foam metal can be stretched in any specific direction before or after compression or during the compression process, and the aspect ratio of the internal holes after stretching is 1:1 to 10:1.

[0042] The porous metal support layer can be prepared in any of the following two ways:

[0043] Cut porous metal directly into required specifications and sizes;

[0044] Grooves arranged parallel to the length or width direction, or arranged at a specific angle to the length or width direction, or grooves intersecting each other on the porous metal support layer, or grooves radiating outward from a certain point on the porous metal support layer are processed on the porous metal by rolling.

[0045] The porous metal support layer can be stretched before or while processing the grooves by rolling, and the aspect ratio of the internal holes after stretching is 1:1 to 10:1.

[0046] After the grooves are machined on the porous metal support layer by rolling, a metal layer can be further electrodeposited on the surface of the porous metal.

[0047] The larger the effective capillary pore size of the absorbent core, the greater its permeability, but an overly large capillary pore size will cause the capillary suction force it generates to become smaller, which is not conducive to the reflux of the working medium; the smaller the effective capillary pore size of the absorbent core, the greater the capillary suction force it generates, but an overly small effective pore size of the absorbent core will cause the permeability of the capillary core to drop sharply, resulting in a sharp increase in the flow resistance of the working medium in the capillary core. In order to make the foam metal absorbent core have a large capillary suction force, permeability, and a small thickness at the same time, in the technical solution of the present invention, by compressing one or more layers of foam metal, by selecting original foam metals with different pore numbers (PPI), surface density, and thickness, different compression ratios, and selecting the same or different pore numbers (PPI), surface density, and thickness of original foam metals when compressing more than two layers of foam metal stacking, so as to adjust the pore shape, pore size, and pore size distribution of the absorbent core, a absorbent core with large capillary suction force, permeability, and small thickness can be obtained. At the same time, as the compression of the foam metal proceeds, the microcolumns formed by the external broken holes are compressed and new closed small holes are re-formed, which enhances the capillary force of the outer pores of the foam metal, promotes the reflux of the liquefied medium, and improves the shortcomings of the prior art. This is because the foam metal structure is a three-dimensional network with random topology. The metal skeleton branches and overlaps each other to form countless interconnected cells. The cell body is composed of 10 to 14 faces, each of which has a hole. The shape of the hole is roughly 3 to 6 polygons, and the part connecting the holes is the pore-struts. When two or more layers of foam metal are stacked together and compressed, the holes inside the foam metal will become flatter and flatter as the compression progresses. If it is continuously compressed, the pore-struts of each layer of foam metal will enter the interior of the adjacent foam metal, dividing the internal holes for a second time to form a foam metal with a new structure. After the above-mentioned process is regulated, liquid-absorbing cores with different capillary suction, permeability and thickness can be designed according to different heat spreader working conditions. When making ultra-thin heat spreaders, liquid-absorbing cores with high capillary suction, permeability and ultra-thin thickness can be provided.

[0048] When the porous medium absorbent core is obtained by compressing the foam metal, the foam metal can be axially stretched before, during or after the compression process. The pore shape of the foam metal is changed from a nearly circular hole to an elongated hole by stretching, thereby enhancing the capillary suction of the absorbent core.

[0049] In the technical solution of the present invention, in order to enhance the penetration ability of the heat spreader and promote the rapid reflux of the working fluid, a loose and porous capillary layer can be deposited on one of the surfaces of the upper and lower shell plates by electroplating, suspended sand composite electroplating, etc., and the side with the capillary layer is used as the liquid absorption core of the heat spreader. By adjusting the electroplating parameters or the particle size of the metal particles used in the suspended sand composite electroplating, the void size of the capillary layer can be adjusted to enhance the reflux ability of the liquid working fluid.

[0050] In the technical solution of the present invention, in order to further enhance the capillary properties of the liquid wick, a metal oxide nanostructure can be prepared on the surface of the liquid wick, including at least one of nanowires, nanoparticles, and nanosheets, so that the surface of the liquid wick has superhydrophilic properties. The superhydrophilic surface has excellent wetting properties, and the working fluid liquid commonly used in the two-phase heat transfer device can spread rapidly on its surface and enter the pores of the microstructure, which shows that the superhydrophilic structure has good capillary suction for the working fluid liquid, and the better the wettability, the stronger the capillary suction. Constructing a layer of superhydrophilic structure on the wall of the liquid wick with a porous structure will greatly increase the capillary pressure of the liquid wick, thereby breaking the limitations of a single liquid wick structure and significantly improving the capillary properties of the liquid wick structure.

[0051] In the technical solution of the present invention, the porous metal support layer plays two main roles: one is to serve as a steam channel, taking advantage of the high porosity and low gas resistance of the foam metal; the other is to serve as a support layer for the heat spreader shell to prevent the heat spreader from structurally collapsing during the vacuuming process and operation. The prior art uses a single foam metal cylindrical block or square block as a support column, and the spacing between the support columns is large, so the support capacity provided is limited. In order to prevent the local collapse of the heat spreader, its upper and lower shell plates also need to use thicker metal foils to provide a certain compressive strength. Therefore, the thickness of the heat spreader manufactured by the prior art cannot be less than 1mm. In the technical solution of the present invention, a support layer is processed using a whole sheet of foam metal. In order to reduce the resistance to steam flow, the technical solution of the present invention also provides a solution for processing various patterned structural grooves on the foam metal by rolling. The center distance of the groove is only 0.05mm to 3mm, so it can provide more support for the upper and lower shell plates, ensuring that the heat spreader structure will not collapse at any time. Therefore, metal sheets with a thickness of less than 0.1mm can be used to make the upper and lower shell plates of the heat spreader, so that the overall thickness of the heat spreader is greatly reduced, and a heat spreader with an overall thickness of less than 1mm can be manufactured. And after the part of the foam metal formed at the bottom of the groove by rolling is compressed, its capillary force becomes larger. When the heat spreader is working, this part of the foam metal at the bottom of the groove can be used as a liquid wick to provide a channel for the reflux of the liquefied chemical, thereby enhancing the heat transfer performance of the heat spreader.

[0052] In the technical solution of the present invention, the porous metal support layer can be processed by rolling grooves on the surface of the porous metal, so it can be continuously processed using a roll-to-roll process. Compared with the solution of using independent block support columns in the prior art, it also has the characteristics of high production efficiency and low cost. Considering that in order to improve the supporting capacity of the porous metal support layer, it is necessary to use a porous metal with a relatively high surface density to improve the structural strength, but the higher the surface density of the porous metal, the more difficult it is to roll the process. Therefore, in the technical solution of the present invention, a porous metal with a lower surface density can also be used. After the grooves are first processed by rolling, a thicker metal layer can be continuously deposited on the surface of the porous metal to improve the structural strength of the porous metal support layer, thereby reducing the difficulty of processing and facilitating large-scale production.

[0053] In summary, in the technical scheme of the present invention, the wick prepared by using electroplating, foam metal compression, foam metal stretching, preparing super hydrophobic structure, etc., has high capillary suction and permeability, and can also have a small thickness. Using a whole sheet of porous metal as a support layer, compared with using support columns separated from each other, it has a stronger structural support ability to ensure that the structure of the soaking plate does not collapse; in order to obtain a smaller steam resistance, a patterned groove can also be prepared on the porous metal using a rolling process, and the part of the porous metal compressed at the bottom of the groove after rolling can also be used as a wick to enhance the reflux capacity of the liquefied substance of the soaking plate. The wick and the support layer in the technical scheme of the present invention can be processed using a roll-to-roll continuous process, and the production efficiency is extremely high, which is suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0054] Figure 1 is a schematic diagram of an ultra-thin vapor chamber in Example 1;

[0055] Figure 2 A schematic diagram of an ultra-thin vapor chamber in Example 2;

[0056] Figure 3 It is a schematic diagram of an ultra-thin vapor chamber in Embodiments 3, 4, 5 and 6;

[0057] Figure 4 A schematic diagram of a porous metal support layer in an ultra-thin vapor chamber in Examples 1 and 3;

[0058] Figure 5 A schematic diagram of a porous metal support layer in an ultra-thin vapor chamber in Example 4;

[0059] Figure 6 A schematic diagram of a porous metal support layer in an ultra-thin vapor chamber in Example 5;

[0060] Figure 7 A schematic diagram of a porous metal support layer in an ultra-thin vapor chamber in Example 6;

[0061] Figure 8 This is a structural diagram of the copper oxide nanosheet with super hydrophilic properties in Example 2. DETAILED DESCRIPTION

[0062] The ultra-thin vapor chamber and the manufacturing method thereof described in the present invention are further described below in conjunction with specific embodiments.

[0063] Embodiment 1:

[0064] like Figure 1An ultra-thin heat spreader is shown, the structure of which is an ultra-thin closed chamber composed of an upper shell plate (11), a lower shell plate (12), a liquid wick (13), a porous metal support layer (14) and a working medium;

[0065] The upper shell plate (11) and the lower shell plate (12) are copper foils with a thickness of 0.05 mm, and a layer of aluminum oxide barrier film is deposited on the outer surface of the copper foils;

[0066] The liquid wick (13) is obtained by sintering copper balls with an average particle size of 0.03 mm on the inner surfaces of the upper shell plate (11) and the lower shell plate (12), and has a thickness of 0.06 mm;

[0067] The porous metal support layer (14) is a patterned structure, disposed between two layers of the liquid wick (13), and uses a copper foam having an open-pore three-dimensional mesh structure, the copper foam having a thickness of 0.4 mm and an average pore diameter of 0.1 mm, and is prepared by providing grooves parallel to the width direction on the copper foam (such as Figure 4 As shown), the groove depth is 0.3mm, the groove bottom width is 0.08mm, and the groove top width is 0.09mm;

[0068] Water is used as the working medium, and the volume of water filled is 110% of the void space of the wick.

[0069] A method for manufacturing an ultra-thin vapor chamber:

[0070] (1) Cutting out the upper shell plate (11) and the lower shell plate (12) according to the size of the heat spreader required by the design;

[0071] (2) Sintering copper balls with an average particle size of 0.03 mm on the inner surfaces of the upper shell plate (11) and the lower shell plate (12) to obtain a porous capillary layer as a liquid wick (13);

[0072] (3) Preparation of the porous metal support layer (14): using a roller pressing method, a groove parallel to the width direction is processed on the foam copper, the groove depth is 0.3 mm, the groove bottom width is 0.08 mm, and the groove top width is 0.09 mm;

[0073] (4) placing the porous metal support layer (14) between the upper and lower layers of the liquid wick (13), connecting the upper and lower shell plates together around the periphery by welding to form a closed inner cavity, and reserving a liquid filling port;

[0074] (5) After evacuation, water is filled into the shell as a working medium. The volume of the water filled is 110% of the void space of the wick. Finally, an ultra-thin heat spreader is obtained by sealing.

[0075] Embodiment 2:

[0076] like Figure 2An ultra-thin heat spreader is shown, the structure of which is an ultra-thin closed chamber composed of an upper shell plate (21), a lower shell plate (22), a liquid wick (23), a porous metal support layer (24) and a working medium;

[0077] The upper shell plate (21) and the lower shell plate (22) are copper foils with a thickness of 0.1 mm;

[0078] The liquid wick (23) is formed by stacking two layers of foam copper (the foam copper specifications are: pore number (PPI) is 95, thickness is 1.8 mm, surface density is 280 g / m 2 ) to obtain a porous medium. The porosity of the compressed copper foam is 70% and its thickness is 0.2 mm. A layer of copper oxide nanosheet structure with super hydrophilic properties is prepared on the surface of the copper foam. The structure of the nanosheet is as follows Figure 8 As shown;

[0079] The porous metal support layer (24) has a single structure and is disposed between two layers of the liquid wick (23). The porous metal support layer (24) is made of nickel foam having an open-pore three-dimensional mesh structure, a thickness of 0.6 mm, and an average pore diameter of 0.08 mm.

[0080] Ethanol was used as the working medium, and the volume of ethanol filled was 110% of the void space of the wick.

[0081] A method for manufacturing an ultra-thin vapor chamber:

[0082] (1) Cutting out the upper shell plate (21) and the lower shell plate (22) according to the size of the heat spreader required by the design;

[0083] (2) Preparation of the liquid wick (23): Two layers of copper foam are stacked and compressed to obtain a porous medium, the porosity of the compressed porous medium is 70% and the thickness is 0.2 mm. The obtained porous medium is welded to the inner surface of the upper and lower shell plates, and then a layer of copper oxide nanosheet structure with super hydrophilic properties is prepared on the surface;

[0084] (3) According to the design requirements, a nickel foam having a thickness of 0.6 mm and an average pore diameter of 0.08 mm is cut to obtain a porous metal support layer (24);

[0085] (4) placing the porous metal support layer (24) between the upper and lower layers of the liquid wick (23), connecting the upper and lower shell plates together around the periphery by welding to form a closed inner cavity, and reserving a liquid filling port;

[0086] (5) After evacuation, ethanol is filled into the shell as a working medium. The volume of the ethanol filled is 80% of the void space of the wick. Finally, an ultra-thin heat spreader is obtained by sealing.

[0087] Embodiment three:

[0088] like Figure 3 An ultra-thin heat spreader is shown, the structure of which is an ultra-thin closed chamber composed of an upper shell plate (31), a lower shell plate (32), a liquid wick (33), a porous metal support layer (34) and a working medium;

[0089] The upper shell plate (31) and the lower shell plate (32) are aluminum foils with a thickness of 0.5 mm, the surface of the aluminum foils is covered with a layer of tin film, and the inner surfaces of the upper and lower shell plates are connected to the liquid wick (33);

[0090] The liquid wick (33) is a porous medium obtained by compressing a layer of copper foam, wherein the copper foam is stretched before compression, and after stretching, the aspect ratio of the internal pore diameter is 3:1, and the porosity of the copper foam after compression is 50% and the thickness is 0.5 mm;

[0091] The porous metal support layer (34) has a patterned structure and is disposed between the two layers of the wick (33). It is made of a copper foam having an open-pore three-dimensional mesh structure, a thickness of 2 mm, and an average pore diameter of 0.5 mm. The copper foam is prepared by providing grooves parallel to the length direction (e.g. Figure 4 As shown), the groove depth is 0.1mm, the groove bottom width is 0.2mm, and the groove top width is 0.3mm;

[0092] Toluene was used as the working medium, and the volume of toluene filled was 110% of the void space of the wick.

[0093] A method for manufacturing an ultra-thin vapor chamber:

[0094] (1) Cutting out the upper shell plate (31) and the lower shell plate (32) according to the size of the heat spreader required by the design;

[0095] (2) Preparation of the liquid wick (33): a layer of foam copper (specifications of the foam copper are: number of pores (PPI) is 50, thickness is 2.2 mm, surface density is 330 g / m 2 ) firstly stretching, after which the aspect ratio of the internal pore size is 3:1, and then compressing the obtained porous medium, the porosity of the compressed porous medium is 50%, and the thickness is 0.5 mm;

[0096] (3) Preparation of the porous metal support layer (34): using a rolling method, a groove parallel to the length direction is processed on the foam copper, wherein the groove depth is 0.1 mm, the groove bottom width is 0.2 mm, and the groove top width is 0.3 mm;

[0097] (4) placing the porous metal support layer (34) between the upper and lower layers of the liquid wick (33), connecting the upper and lower shell plates together around the periphery by welding to form a closed inner cavity, and reserving a liquid filling port;

[0098] (5) After evacuation, toluene is filled into the shell as a working medium. The volume of the toluene filled is 110% of the void space of the wick. Finally, an ultra-thin heat spreader is obtained by sealing.

[0099] Embodiment 4:

[0100] like Figure 3 An ultra-thin heat spreader is shown, the structure of which is an ultra-thin closed chamber composed of an upper shell plate (31), a lower shell plate (32), a liquid wick (33), a porous metal support layer (34) and a working medium;

[0101] The upper shell plate (31) and the lower shell plate (32) are made of copper-nickel alloy foil with a thickness of 1 mm, and the inner surfaces of the upper and lower shell plates are connected to the liquid wick (33);

[0102] The liquid wick (33) is prepared by filling a layer of foam copper (the foam copper specifications are: pore number (PPI) is 110, thickness is 2.5 mm, surface density is 380 g / m 2 ) and then compressed and sintered to obtain a porous medium with a porosity of 30% and a thickness of 1.5 mm;

[0103] The porous metal support layer (34) has a patterned structure and is disposed between the two layers of the wick (33). It is a copper foam with a three-dimensional mesh structure having an open hole, a thickness of 5 mm, and an average pore diameter of 0.8 mm. The copper foam is provided with grooves (such as Figure 5 As shown), the groove depth is 4.5mm, the groove bottom width is 9mm, and the groove top width is 10mm;

[0104] Ammonia is used as the working medium, and the volume of ammonia filled is 110% of the void space of the wick.

[0105] A method for manufacturing an ultra-thin vapor chamber:

[0106] (1) Cutting out the upper shell plate (31) and the lower shell plate (32) according to the size of the heat spreader required by the design;

[0107] (2) Preparation of the liquid wick (33): Silver-coated copper powder with an average particle size of 0.08 mm is uniformly mixed with a binder, and then filled into the internal gap of a layer of foam copper by spraying, and then compressed and sintered to form a porous medium. The liquid wick is then welded to the inner surface of the upper and lower shell plates;

[0108] (3) Preparation of the porous metal support layer (34): using a rolling method, grooves parallel to the length and width directions and arranged crosswise with each other were prepared, wherein the groove depth was 4.5 mm, the groove bottom width was 9 mm, and the groove top width was 10 mm;

[0109] (4) placing the porous metal support layer (34) between the upper and lower layers of the liquid wick (33), connecting the upper and lower shell plates together around the periphery by welding to form a closed inner cavity, and reserving a liquid filling port;

[0110] (5) After evacuation, ammonia is filled into the shell as the working medium. The volume of ammonia filled is 110% of the void space of the wick. Finally, an ultra-thin heat spreader is obtained by sealing.

[0111] Embodiment five:

[0112] like Figure 3 An ultra-thin heat spreader is shown, the structure of which is an ultra-thin closed chamber composed of an upper shell plate (31), a lower shell plate (32), a liquid wick (33), a porous metal support layer (34) and a working medium;

[0113] The upper shell plate (31) and the lower shell plate (32) are 0.8 mm thick and are artificial graphite sheets with copper thin films deposited on the surfaces, wherein the thickness of the copper thin films is 0.2 mm and the thickness of the artificial graphite sheets is 0.4 mm;

[0114] The liquid wick (33) is formed by filling copper-nickel alloy balls with an average particle size of 0.05 mm into two stacked layers of foam copper with different specifications (the foam copper specifications are: pore number (PPI) of 85, thickness of 1.2 mm, surface density of 320 g / m 2 , and the number of holes (PPI) is 75, the thickness is 1.6mm, and the surface density is 250g / m 2 ) and then compressed and sintered to obtain a porous medium with a porosity of 60% and a thickness of 0.8 mm.

[0115] The porous metal support layer (34) has a patterned structure and is disposed between the two layers of the liquid wick (33). It is a nickel foam with a three-dimensional mesh structure having an open hole, a thickness of 6 mm, and an average pore diameter of 1 mm. Two groups of cross-arranged grooves are prepared on the nickel foam, one group of grooves is at an angle of 45° to the length direction, and the other group of grooves is parallel to the width direction (such as Figure 6 As shown), the groove depth is 1mm, the groove bottom width is 2mm, and the groove top width is 4mm;

[0116] Acetone was used as the working medium, and the volume of acetone filled was 120% of the void space of the wick.

[0117] A method for manufacturing an ultra-thin vapor chamber:

[0118] (1) Cutting out the upper shell plate (31) and the lower shell plate (32) according to the size of the heat spreader required by the design;

[0119] (2) Preparation of the liquid wick (33): Copper-nickel alloy balls with an average particle size of 0.05 mm are uniformly mixed with a binder, and then filled into the internal gaps of two stacked layers of foam copper of different specifications by spraying, and then compressed and sintered to obtain a porous medium. The liquid wick is then welded to the inner surface of the upper and lower shell plates;

[0120] (3) Preparation of the porous metal support layer (34): using a roller pressing method, two groups of cross-arranged grooves are prepared on the nickel foam, one group of grooves is at an angle of 45° to the length direction, and the other group of grooves is parallel to the width direction. The groove depth is 1 mm, the groove bottom width is 2 mm, and the groove top width is 4 mm;

[0121] (4) placing the porous metal support layer (34) between the upper and lower layers of the liquid wick (33), connecting the upper and lower shell plates together around the periphery by welding to form a closed inner cavity, and reserving a liquid filling port;

[0122] (5) After evacuation, acetone is filled into the shell as a working medium. The volume of acetone filled is 120% of the void space of the wick. Finally, an ultra-thin heat spreader is obtained by sealing.

[0123] Embodiment six:

[0124] like Figure 3 An ultra-thin heat spreader is shown, the structure of which is an ultra-thin closed chamber composed of an upper shell plate (31), a lower shell plate (32), a liquid wick (33), a porous metal support layer (34) and a working medium;

[0125] The upper shell plate (31) and the lower shell plate (32) are copper foils with a thickness of 1.5 mm, and the copper foils are single crystal copper foils obtained by heat treatment of rolled copper foils. The inner surfaces of the upper and lower shell plates are connected to the liquid wick (33);

[0126] The liquid wick (33) is a porous medium obtained by stacking and compressing three layers of foam metals of different specifications. The porosity of the compressed foam metal is 40% and the thickness is 1 mm. The three layers of foam metals of different specifications are: pore number (PPI) of 35, thickness of 2.0 mm, and surface density of 300 g / m 2 The foam copper has a porosity (PPI) of 95, a thickness of 1.2 mm, and a surface density of 350 g / m 2 The foam copper has a pore count (PPI) of 110, a thickness of 1.5 mm, and a surface density of 280 g / m 2 Nickel foam;

[0127] The porous metal support layer (34) has a patterned structure and is disposed between two layers of the liquid wick (33). The foam copper has a three-dimensional mesh structure with an open hole, a thickness of 8 mm, and an average pore diameter of 2 mm. The foam copper is stretched, and the aspect ratio of the internal pore diameter after stretching is 2:1. Then, a groove (such as Figure 7 As shown), the groove depth is 2mm, the groove bottom width is 5mm, and the groove top width is 6mm;

[0128] Methanol was used as the working medium, and the volume of methanol filled was 130% of the void space of the wick.

[0129] A method for manufacturing an ultra-thin vapor chamber:

[0130] (1) Cutting out the upper shell plate (31) and the lower shell plate (32) according to the size of the heat spreader required by the design;

[0131] (2) Fabrication of the liquid wick (33): Three layers of foam metals of different specifications are stacked and compressed to obtain a porous medium having a porosity of 40% and a thickness of 1 mm. The liquid wick is then welded to the inner surfaces of the upper and lower shell plates;

[0132] (3) Preparation of porous metal support layer (34): The copper foam is first stretched to a length-to-diameter ratio of 2:1. Then, a continuous molding method is used to form a groove radiating outward from a central circle with a diameter of 2 mm on the copper foam (e.g. Figure 7 As shown), the groove depth is 2mm, the groove bottom width is 5mm, and the groove top width is 6mm;

[0133] (4) placing the porous metal support layer (34) between the upper and lower layers of the liquid wick (33), connecting the upper and lower shell plates together around the periphery by welding to form a closed inner cavity, and reserving a liquid filling port;

[0134] (5) After evacuation, methanol is filled into the shell as a working medium. The volume of the methanol filled is 130% of the void space of the wick. Finally, an ultra-thin heat spreader is obtained by sealing.

Claims

1. A method for manufacturing an ultra-thin vapor chamber, characterized in that: The following steps are involved:

1. Production of upper and lower shell plates; (ii) The liquid wick is manufactured by the following method: it is obtained by compressing two or more layers of superimposed foam metal with an average thickness of 0.4 mm to 3 mm, and the porosity of the compressed foam metal is 30% to 90%; (3) connecting the metal sheets serving as the upper shell plate and the lower shell plate to the liquid wick; (iv) Preparation of porous metal support layer; (5) placing the porous metal support layer between the upper shell plate and the lower shell plate connected to the wick; (vi) Assemble using welding technology, weld the upper and lower shell plates together around the perimeter, and reserve a liquid filling port; (VII) Filling the working medium into the closed inner cavity between the upper shell plate and the lower shell plate; (8) Welding and sealing; In the manufacturing process of the absorbent core, when the absorbent core is obtained by compressing the foam metal, the foam metal is stretched in any specific direction before or after the compression or during the compression process, and the aspect ratio of the internal holes after the stretching is 1:1 to 10:1; The porous metal support layer is manufactured in the following manner: grooves arranged parallel to the length or width direction, or grooves arranged at a specific angle to the length or width direction, or grooves intersecting each other on the porous metal support layer, or grooves radially arranged outward from a certain point as the center point on the porous metal support layer are processed on the porous metal by rolling; The ultra-thin heat spreader is an ultra-thin closed chamber composed of an upper shell plate, a lower shell plate, a liquid wick, a porous metal support layer and a working medium; (1) The thickness of the upper shell plate and the lower shell plate is 0.01 mm to 1.0 mm, and the material is metal and its alloy or non-metal and compound material with good thermal conductivity and airtightness; (2) The thickness of the liquid absorbent core is 0.02 mm to 1.5 mm; (3) The porous metal support layer has an open-pore three-dimensional mesh structure with a thickness of 0.1 mm to 15 mm, and its structure is a patterned structure, wherein: the patterned structure means that a groove is provided on the porous metal support layer, the groove depth is 0.02 mm to 14.5 mm, the groove bottom width is 0.05 to 30 mm, and the groove top width is 0.05 to 30 mm; (4) The working medium is filled in the closed inner cavity of the shell, and the working medium is a liquid material, and its volume accounts for 50% to 300% of the void space of the liquid wick; The liquid-absorbing core comprises a hydrophilic metal oxide nanostructure on the surface thereof, and the morphology of the metal oxide nanostructure comprises at least one of nanowires, nanoparticles or nanosheets.

2. The method for manufacturing an ultra-thin vapor chamber according to claim 1, characterized in that: The porous metal support layer is stretched before or while the grooves are processed by rolling, and the aspect ratio of the internal holes is 1:1 to 10:1 after stretching.

3. The method for manufacturing an ultra-thin vapor chamber according to claim 1, characterized in that: After grooves are machined on the porous metal support layer by rolling, a metal layer is continuously electrodeposited on the surface of the porous metal.

4. The method for manufacturing an ultra-thin vapor chamber according to claim 1, characterized in that: The upper shell plate and the lower shell plate are composite materials made of any one or more of copper, aluminum, silver, nickel, titanium, carbon material, mica or boron nitride.

5. The method for manufacturing an ultra-thin vapor chamber according to claim 1, characterized in that: The two or more superimposed foam metal layers used to form the liquid absorbing core are composed of the same material and specification, or are composed of different numbers of holes, thicknesses, surface densities, and materials.

6. The method for manufacturing an ultra-thin vapor chamber according to claim 1, characterized in that: The porous metal support layer is a porous foam metal with an open-pore three-dimensional network structure obtained by depositing a metal layer on the surface of a polyurethane sponge and then sintering and reducing it.

7. The method for manufacturing an ultra-thin vapor chamber according to claim 1, characterized in that: The volume of the working medium accounts for 80%-150% of the void space of the wick.

8. The method for manufacturing an ultra-thin vapor chamber according to claim 1, characterized in that: The working medium is any one of ammonia, freon, ethane, acetone, butanone, water, ethanol, methanol, toluene, Doheny-A or Doheny-E, or a mixture of several thereof.

9. A method for manufacturing an ultra-thin vapor chamber according to claim 1 or 4, characterized in that: The upper shell plate and the lower shell plate include metal sheets obtained through rolling and electrolysis processes, or single crystal metals obtained by heat treatment of rolled metal sheets, or liquid metals.

10. The method for manufacturing an ultra-thin vapor chamber according to claim 4, characterized in that: The carbon material includes artificial graphite, natural graphite or diamond.

11. A method for manufacturing an ultra-thin vapor chamber according to claim 10, characterized in that: The artificial graphite comprises a composite material obtained by depositing a metal layer on the surface of an artificial synthetic graphite sheet by using vacuum plating, electrodeposition or a combination of the two processes, wherein the artificial synthetic graphite sheet is made of a polyimide film subjected to high-temperature carbonization and graphitization treatment.

12. The method for manufacturing an ultra-thin vapor chamber according to claim 3, characterized in that: The metal layer is any one of copper, tin, silver and titanium or a composite material made of several materials.

Citation Information

Patent Citations

  • Manufacturing method of soaking plate with ultrathin foam silver as liquid absorbing core

    CN104896983A